An Ethnozoological Study: Utilization of Sharks Fishermen's Community of Brondong Village, Lamongan Regency - Setyawan, Dwi; Farid, Saif Aiman; Hadi, Samsun; Permana, Fendy Hardian; Prihanta, Wahyu (Universitas Gadjah Mada, 2024)
The problems studied focus on the influence of ethnozoological knowledge and family economic Status on the use of endangered sharks by the people of Brondong village. The Data were taken in the form of (1) ethnozoological knowledge of the community, (2) Family economic status, (3) Attitudes, and (4) Shark utilization behavior. Data collection is done by survey method with the help of questionnaire, structured interview, and direct observation. Path - analysis is performed to determine the relationship of the proposed variables. Not only that, the relationship of variables can also be explained by descriptive analysis. The results showed that the Brondong ethnic community still adheres to Airlangga and Majapahit culture by maximizing fishing activities, one of which is the behavior of shark utilization for sale and consumption. While the results of Block 1 path analysis showed a significant influence of ethnozoological knowledge on attitudes, amounting to 0.446. While the results of Block 2 showed the influence of attitudes towards shark utilization behavior, had a significant path coefficient of 0.253. It is concluded that ethnozoological knowledge affects indirectly the utilization of shark behavior by passing attitude.